2021
DOI: 10.20944/preprints202105.0221.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D Printing Part 1 - A History and Literature Review Of 3D Printing in Dentistry

Abstract: Introduction: The term 3D printing is commonly used to depict an assembling method whereby the final form of an object is the result of the addition of different layers to build the frame of an object. This procedure is more accurately portrayed as additive manufacturing and is likewise alluded to as fast prototyping. The term 3D printing, in any case, is generally new and has been an active part of current developments in Dentistry. Much publicity encompasses the evolution of 3D printing, which is hailed as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Polymers make up the majority of the 3D printing materials used in dental restorations, which replace lost teeth and tooth structure. In contrast to ceramics and metals, the chemical and physical properties of polymers are characterized by elasticity and tensile strength, which may offer the high-performance and longlasting qualities required for use as a dental restorative material [11]. The transverse strength and elastic modulus of the resin were both significantly impacted by a change in the polymerization temperature [17].…”
Section: Sla Materials Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Polymers make up the majority of the 3D printing materials used in dental restorations, which replace lost teeth and tooth structure. In contrast to ceramics and metals, the chemical and physical properties of polymers are characterized by elasticity and tensile strength, which may offer the high-performance and longlasting qualities required for use as a dental restorative material [11]. The transverse strength and elastic modulus of the resin were both significantly impacted by a change in the polymerization temperature [17].…”
Section: Sla Materials Overviewmentioning
confidence: 99%
“…Threedimensional printing technology have created a variety of dental prosthesis using polymer materials in orthodontic treatment, including denture bases, fake teeth, temporary crowns, bridge and crown facings, and implant caps. Studies have shown that polymers are used in 3D printing technology for dental applications, such as the manufacturing and intervention of implant fixtures, maxillofacial reconstruction, and metal bridges [11]. The majority of resin compositions contain inert dyes, which absorb incoming light and improve polymerization control.…”
Section: Sla Materials Overviewmentioning
confidence: 99%
See 2 more Smart Citations